Development of a Premarital Education Package Based on Transactional Analysis Theory - Rahmati, Fahimeh; Mosavi, Sayed Esmaeil; Yousefi, Zahra (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of the present study was to develop a premarital education package based on Transactional Analysis theory.Methods and Materials: The scope of this research encompassed all texts related to the psychological theory of Transactional Analysis. The selection of texts was purposefully done from Eric Berne's theoretical works within the timeframe of 1990 to 2024. The criterion for the number of texts was based on the principle of data saturation. The method of data collection involved line-by-line examination of texts, guided by questions relevant to the components suitable for premarital counseling in this theory. The data obtained from the text reviews were analyzed using the conventional content analysis method by Hsieh and Shannon (2005).Findings: The results of the content analysis indicated that in Eric Berne's theory, 1) the ego states (Adult, Parent, and Child), life script (characteristics of the life script, elements of the life script, and four life positions), and transactions (complementary transactions, crossed transactions, ulterior transactions, and games) are appropriate for alignment with premarital education. Subsequently, these concepts were integrated theoretically using the method by Yousefi and Golparvar (2023), and ultimately, the premarital education package was designed and prepared.Conclusion: Overall, considering the process of deriving this education, it can be said that it is content-valid and can be evaluated at the level of designing an educational package and conducting experimental reviews on marriage-related constructs.